Original paperAllergy to propolis in Polish beekeepers - Basista, Katarzyna M.; Filipek, Barbara (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2012)
Introduction : According to the literature propolis is a non-toxic and safe substance. However, propolis can induce allergy. Beekeepers may be the group most affected by contact allergy and propolis is an occupational contact allergen for them. Aim: To determine the prevalence of propolis contact allergy in beekeepers and theirs families and its possible association with other coexistent conditions. Material and methods : The questionnaire ‘Allergy to propolis among beekeepers’ was distributed to beekeepers by hand through the Beekeepers Associations, especially the Provincial Association of Apiarists in Krakow. The study was conducted on adults of both genders who had given informed consent to participate in the study. The program Statistica was used for data management and statistical analysis. Results : A total of 2540 questionnaires were distributed, including 1360 questionnaires from Malopolska region. Five hundred and fifty-eight questionnaires were returned, including 345 from Malopolska region. The response rate was 21.97% (25.4% Malopolska region). Among 558 beekeepers propolis contact allergy occurred in 17 cases (3.05%). Four hundred anf four of 558 beekeepers used propolis as a therapeutic agent. Eleven of 404 (2.72%) beekeepers reported propolis allergy. Only 5 beekeepers reported concomitant propolis allergy after contact with this substance during beekeeping and using propolis as a therapeutic agent. Among 2205 members of families who were using propolis only 14 patients (0.63%) reported propolis allergy. Conclusions : Allergy to propolis in Polish beekeepers does not seem to be a common phenomenon.